PERANCANGAN DAN ANALISIS RANGKA MESIN DESKTOP CNC MILLING - Didi Widya Utama (Jurnal Ilmiah Teknik Mesin POROS, 2018)
The need of machine tools is growing in Indonesia every years, this because of the increasing need of high quality product and short product manufacturing time are the answer for the market needed. CNC machine is a numerical method which the computer is used to control the machine tools, in Indonesia itself are increasing its usage from large scale industry to home industry and as well as in education sector. Education sector need to be up to date to the technology to empowering their students in order to catch up in the technology growth. Investment in CNC machine tools is consider as a high investment for education institution, and industrial CNC machine tools also bulky so it difficult to move around which are difficult to bring it in classroom. To overcome the problem in this paper will discuss about design and analysis of prototype CNC milling machine tool which has working area of 328 mm × 245mm × 100mm and can withstand the force of cutting of 0.044Nm. In this paper also discuss about design and analysis of the machine tools frame using finite element method. Result from the frame analysis with the load from Z direction of 10 kg of load shows the maximum displacement is 0.07558mm and maximum stress is 0.09178 Mpa.